Catalytic Hydrogenation Properties of Noncrystalline Ni-B Nanotubes - LIU, FUPING; LU, MING; LI, FENG (Asian Journal of Chemistry, 2010)
Noncrystalline Ni-B nanotubes were prepared by reduction of nickel chloride with an aqueous solution of sodium using lyotropic non-ionic-anionic mixed surfactant liquid crystals as template. In comparison with other Ni-based catalysts, the noncrystalline Ni-B nanotubes exhibited higher activity and better selectivity. The relationships between catalysts performance and the structure of catalysts, surface electronic state of catalysts were discussed based on various characterizations including X-ray diffraction, transmission electron micrographs (TEM) and selected area electron diffraction (SAED).